Relationship between maternal health behavior and physical growth pattern of ‎children under one year referred to health departments of Rasht city - afsaneh pasha; tayebeh hasan tehrani; mino mitra chehrzad; zahra atrkar roushan (Journal of Holistic Nursing and Midwifery)
Introduction: Physical growth in infants is the most important health indicator. In fact many ‎factors influence infants physical growth. Because of complete dependence of infants to their ‎mothers and role of mother care and health behavior is important for health promotion.‎